The Cathodic Cleavage of the Nitrobenzoyl Group from Protected Aliphatic Amines in N,N-Dimethylformamide - Jorge, Sônia Maria Alves [UNESP]; Campos, Pedro Maia de; Stradiotto, Nelson Ramos [UNESP] (Sociedade Brasileira de Química, 1999)
A redução eletroquímica de aminas alifáticas protegidas pelo grupo 4- e 3-nitrobenzoila em N,N-dimetilformamida foi estudada. Os compostos são reduzidos em duas etapas catódicas. A primeira em aproximadamente -1 V vs. ECS ocorre com a formação de radicais ânions relativamente estáveis, envolvendo a transferência de um elétron. A redução ao diânion ocorre no intervalo de -1,5 e -2,0 V vs. ECS por um processo ECE, conduzindo à clivagem da ligação CN com rendimentos acima de 50%.

The electrochemical reduction of aliphatic amines protected by the 4- and 3- nitrobenzoyl group in N,N-dimethylformamide was reported. The compounds are reduced in two cathodic steps. The first one at about -1 V vs. SCE occurs with the formation of the rather stable anion radicals, involving one electron transfer . The reduction to dianion occurs at potentials between -1.5 and -2.0 V vs. SCE by an ECE process and leads to cleavage of the CN bond in yields above 50%.
Keywords: nitrobenzoyl group; cathodic cleavage; aliphatic amines